Serum biochemical and inflammatory cytokines in a rat model of metabolic syndrome - Yeldu, Mohammed Haruna; Mus’ab, Ahmed (Asian Journal of Medical Sciences, 2020)
Background: Metabolic syndrome (MetS) is a combination of cardio-metabolic risk factors including obesity, hyperglycaemia, dyslipidaemia, oxidative stress and hypertension. Aims and Objectives: This study was aimed at determining the serum concentrations of biochemical and inflammatory cytokines and assesses the correlation between the biochemical and inflammatory cytokines in a rat model of metabolic syndrome. Materials and Methods: Twenty rats were divided into 2 groups of 10 each: control (fructose untreated) and the fructose treated group. MetS was induced by oral administration of 10% fructose in water for 32 weeks. At the end of the experiment, rats were fasted for 12 hours and blood samples collected and body weight, body mass index (BMI), fasting blood glucose (FBG), serum lipid profile, interleukin-6 (IL-6), interleukin-10 (IL-10), tumour necrosis factor-α (TNF-α) were measured using standard techniques. Result: Result indicated significantly (P< 0.05) increased FBG, body weight, BMI, serum TC and LDL-C while, HDL-C levels significantly (P< 0.05) decreased in MetS group compared with controls. However, the levels of VLDL-C, TG and AIX were not significantly (P > 0.05) different between the groups. Significantly (P< 0.05) increased serum IL-6, IL-10 and TNF-α were observed in MetS group compared with controls. Serum IL-10 and TNF- α were inversely correlated with BMI. Serum IL-10 negatively correlated with FBG while, IL-6 was not correlated with either of BMI and FBG.Serum AIX and VLDL-C were positively correlated with TG while, HDL-C level was inversely correlated with TG. With the exception of serum LDL-C which positively correlated with TC, significant correlation was not established between serum TC and each of AIX, HDL-C and VLDL-C. Conclusion: The rat model of MetS was established after treatment with 10% fructose in water. This plays an important role in the pathogenesis of components of metabolic syndrome, including dyslipidaemia, hyperglycaemia and obesity; and serum IL-6, IL-10 and TNF- α are raised in metabolic syndrome and this underscores the role of these cytokines in inflammation associated with metabolic syndrome.